Teacher and student readiness using E-learning and M-learning - Ramadiani Ramadiani; Azainil Azainil; Achmad Nizar Hidayanto; Dyna Marissa Khairina; Muhammad Labib Jundillah (Institute of Advanced Engineering and Science, 2020)
This research is about the readiness of teachers and students to develop E-learning and M-learning for the learning process. Before developing and implementing an E-learning and M-learning system, it is important to ensure the user's readiness for the technology. Users' perceptions will affect their willingness and readiness to use the system. This study aims to investigate the teachers and students perceptions about E-learning and M-learning, ensuring their readiness to involve in developing online learning process. The study was conducted by survey methods, questionnaires and direct interviews with prospective users in the schools, students, teachers and principals. Research respondents were from Junior High School and Senior High Schools in Samarinda. The questionnaires will be carried out in two stages, before and after the development of E-learning and M-learning systems. The findings obtained from this study indicate that research partner schools are ready and able to participate in developing E-learning and M-learning systems.